2016
DOI: 10.1002/bem.21992
|View full text |Cite
|
Sign up to set email alerts
|

1950 MHz radiofrequency electromagnetic fields do not aggravate memory deficits in 5xFAD mice

Abstract: The increased use of mobile phones has generated public concern about the impact of radiofrequency electromagnetic fields (RF‐EMF) on health. In the present study, we investigated whether RF‐EMFs induce molecular changes in amyloid precursor protein (APP) processing and amyloid beta (Aβ)‐related memory impairment in the 5xFAD mouse, which is a widely used amyloid animal model. The 5xFAD mice at the age of 1.5 months were assigned to two groups (RF‐EMF‐ and sham‐exposed groups, eight mice per group). The RF‐EMF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Further, following 7 months of RF-EMF exposure in young adult mice, no changes were observed in protein oxidative damage in mouse brains, indicating that chronic RF-EMF exposure might not induce detrimental effects on young-adult mice [ 46 ]. Additionally, previous reports indicated that RF-EMF did not affect memory or anxiety-related behaviors in either young-adult [ 39 , 45 , 47 ] or aged animals [ 41 , 48 ]. To examine the effects of RF-EMFs on basic locomotor activity, we performed an open field test.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, following 7 months of RF-EMF exposure in young adult mice, no changes were observed in protein oxidative damage in mouse brains, indicating that chronic RF-EMF exposure might not induce detrimental effects on young-adult mice [ 46 ]. Additionally, previous reports indicated that RF-EMF did not affect memory or anxiety-related behaviors in either young-adult [ 39 , 45 , 47 ] or aged animals [ 41 , 48 ]. To examine the effects of RF-EMFs on basic locomotor activity, we performed an open field test.…”
Section: Discussionmentioning
confidence: 93%
“…However, other studies have reported that exposure to 900–2450 MHz signals did not induce spatial or non-spatial memory impairment in rats [ 43 ] or mice [ 44 ]. Previous studies reported that sub-chronic RF-EMF exposure (during 3 months) did not alter locomotor activity and glial cells (GFAP-positive astrocyte and Iba1-positive microglia) upon exposure of young mice (12 weeks old) to RF-EMF [ 45 ]. Further, following 7 months of RF-EMF exposure in young adult mice, no changes were observed in protein oxidative damage in mouse brains, indicating that chronic RF-EMF exposure might not induce detrimental effects on young-adult mice [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The radial maze and Morris water maze test showed that learning and memory functions were reduced in rats exposed to 2,450 MHz EMF (Lai et al ., 1994; Wang and Lai, 2000), but no changes of working memory were observed in the radial maze test following whole body exposure for 45 minutes for 10 days at 2,450 MHz, 0.6 W/kg SAR (Cassel et al ., 2004; Cobb et al ., 2004) and in the Y-maze, Morris water maze, and novel object recognition memory test after exposed to 1950 MHz electromagnetic fields (SAR 5 W/kg, 2 h/day, 5 days/week) for 3 months (Son et al ., 2016). Recognition memory was studied using the object recognition test (Mortazavi et al ., 2014) using a head-only exposed mouse (900 MHz GSM, 1 and 3.5 W/kg SAR).…”
Section: Effects Of Emf On Learning and Memorymentioning
confidence: 99%
“…Many studies have been carried out to discern whether RF-EMF exposure affects the cognitive functions of the brain. The results have revealed that RF-EMF exposure can lead to positive beneficial effects [11][12][13][14][15], negative harmful effects [16,17], or no effects [1,[18][19][20]. In AD transgenic animal models, positive beneficial effects after long-term RF-EMF exposure were usually observed [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%